Antiribonucleoprotein antibodies in connective tissue diseases: estimation by counterimmunoelectrophoresis. Issue 6061 (5th March 1977) - Bresnihan, B; Bunn, C; Snaith, M L; Hughes, G R
Abstract : One hundred and seventy-two patients with various connective tissue diseases were investigated for the presence of serum antibodies to extractable nuclear antigen (ENA) and its major components, ribonucleo-protein (RNP) and Sm antigen. The counter-immunoelectrophoresis assay allowed independent detection and measurement of antibodies to the different components. All 13 patients with mixed connective tissue disease (MCTD) had anti-RNP antibody in high titres, 16% of patients with systemic lupus erythematosus (SLE) had low titres, and none of the patients with scleroderma had anti-RNP antibody. MCTD seems to be more benign than either SLE or scleroderma. The counterimmunoelectrophoresis assay is a simple and sensitive technique for confirming the diagnosis.